A SURVEY OF THE MUSICAL PREFERENCES OF YOUNG ADOLESCENTS NEWLY ADMITTED TO THE MEDICAL SCHOOL - R.SOBANA; K.JAIGANESH; P.BHARATHI (International Journal of Pharma and Bio Sciences, 2013)
To explore the association between musical preferences and the stress- relieving and/or enhancing reading ability of the preferred class of musical items. 60 adolescents (30 males and 30 females of I MBBS students of a private medical college in Puducherry) were given a single exposure of Rag Bilahari in folk style for 20 minutes, after which they were asked to describe their subjective feelings evoked on listening music which was analyzed with their individual musical preferences. The majority among the adolescent group felt that the musical piece would “reduced their stress” have a preference for folk tune (“reflective & complex” musical dimension of Rentfrow & Gosling) As most of the females felt the music is relaxing is significantly greater than males, we can presume females use music for emotional purpose. Majority of participants belong to the “reflective & complex” musical dimension and feel the music reduces their stress and would enhance their reading ability.